2018
DOI: 10.2105/ajph.2017.304188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Interventions on Other Drug Use in the Cherokee Nation

Abstract: Nonalcohol drug use was consistently reduced as a result of 2 theoretically and operationally distinct alcohol prevention strategies. Evaluations of alcohol prevention efforts should continue to include other drug use to understand the broader effects of such interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Several studies have shown the efficacy of Environmental Prevention strategies to reduce community alcohol problems, including underage drinking, by reducing commercial alcohol availability (Holder et al, 2000;Treno, Gruenewald, Lee, & Remer, 2007;Treno & Lee, 2002;Wagenaar, Toomey, & Erickson, 2005). However, few investigators have described interventions on alcohol use among AI/AN youths (see Cheadle et al, 1995;Gabriel, Leichtling, Bolan, & Becker, 2013;Kulis, Ayers, & Harthun, 2017;May & Moran, 1995;Usera, 2017;Wagenaar, Livingston, Pettigrew, Kominsky, & Komro, 2018;Whitesell et al, 2012;Williams & Perry, 1998). A few studies have included AI/ANs in the study design but were not powered to test for effects that might be specific to the AI/AN sample (Livingston et al, 2018;Perry et al, 2000;Perry et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the efficacy of Environmental Prevention strategies to reduce community alcohol problems, including underage drinking, by reducing commercial alcohol availability (Holder et al, 2000;Treno, Gruenewald, Lee, & Remer, 2007;Treno & Lee, 2002;Wagenaar, Toomey, & Erickson, 2005). However, few investigators have described interventions on alcohol use among AI/AN youths (see Cheadle et al, 1995;Gabriel, Leichtling, Bolan, & Becker, 2013;Kulis, Ayers, & Harthun, 2017;May & Moran, 1995;Usera, 2017;Wagenaar, Livingston, Pettigrew, Kominsky, & Komro, 2018;Whitesell et al, 2012;Williams & Perry, 1998). A few studies have included AI/ANs in the study design but were not powered to test for effects that might be specific to the AI/AN sample (Livingston et al, 2018;Perry et al, 2000;Perry et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, few investigators have described interventions on alcohol use among AI/AN youths (see Cheadle et al, 1995;Gabriel, Leichtling, Bolan, & Becker, 2013;Kulis, Ayers, & Harthun, 2017;May & Moran, 1995;Usera, 2017;Wagenaar, Livingston, Pettigrew, Kominsky, & Komro, 2018;Whitesell et al, 2012;Williams & Perry, 1998). A few studies have included AI/ANs in the study design but were not powered to test for effects that might be specific to the AI/AN sample (Livingston et al, 2018;Perry et al, 2000;Perry et al, 1996). In one of those studies, community-level and individual approaches were employed and the 2-year intervention resulted in significant reductions in alcohol use (Komro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous NIH-funded prevention trial in the Cherokee Nation, we found that an alcohol-focused school-and community-based preventive intervention reduced alcohol use among adolescents, but also had bene cial spillover effects that reduced other drug use, including prescription drug misuse [18,19]. Other prevention trials have also found that involving multiple community systems is effective for the prevention of drug use among adolescents and young adults [20,21].…”
Section: Introductionmentioning
confidence: 92%
“…This speaks to the broad accessibility of CONNECT to schools with limited support staff, but it also ensures effective delivery of a tested alcohol use prevention program to schools with limited resources. Schools can select key teachers, coaches or support staff to be trained in motivational interviewing and the CONNECT program, and dedicate a portion of the effort to program implementation. CONNECT is appropriate for schools with diverse student populations. CONNECT implementers can be trained to be sensitive and promote student's cultural identity. Although CONNECT was focused on alcohol, reductions in other drug use occurred following implementation . Schools can implement CONNECT for alcohol and other drug prevention.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…• Although CONNECT was focused on alcohol, reductions in other drug use occurred following implementation. 40 Schools can implement CON-NECT for alcohol and other drug prevention.…”
Section: Implications For School Healthmentioning
confidence: 99%